A Prophosed Improvement of Service Quality Using Service Quality (Servqual) Model and Flower of Service Model - Muhammad reza Palevy; Dewi Shofi Mulyati (Bandung Conference Series: Industrial Engineering Science, 2023)
Abstract. PT Triadi Bersama with the Anteraja brand, is a company engaged in the delivery of goods that serves the delivery of goods or documents to all regions in Indonesia. At one of the Anteraja shipping centers in the Greater Bandung area, located in Sukasari, they often receive complaints from customers. Complaints that occurred in 2018 to 2021 have increased. The number of customer complaints about the poor service provided by Anteraja is very influential on customer confidence in the quality of the delivery provided and also the decreased number of transactions. To identify problems consisting of factors that affect these services and service attributes that need to be identified using the ServQual (ServiceQuality) model and the flower of service model for proposed improvements and then to group the company's services which are the core strength and support for the company's business. Based on calculations performed using the Service Quality model, it can be seen that there are 20 service attributes that determine customer satisfaction with Anteraja's delivery service. The service attribute is based on the TERRA dimension factor. Service attributes that have a negative gap are 5 service attributes whose performance is not in accordance with customer expectations. The five service attributes are given a solution using the flower of service method. This method categorizes services based on three categories, namely core products, additional services that make it easier, and additional services that strengthen by looking at the priorities of the services that must be improved. The proposed improvements are to give sanctions or warnings by superiors to employees who are not honest and act unfairly to customers, also give warnings to employees who are not serious in doing their work, conduct briefings before the store opens, synchronize databases in the warehouse and in the Admin, and provide training to customer service on how to deal with customers Abstrak. PT Triadi Bersama dengan merek Anteraja, merupakan sebuah perusahaan yang bergerak di bidang pengiriman barang yang melayani pengiriman barang ataupun dokumen keseluruh wilayah di Indonesia. Pada salah salah satu pusat shipping Anteraja area Bandung raya yang berlokasi di Sukasari sering menerima keluhan dari pelanggan. Keluhan yang terjadi pada tahun 2018 sampai tahun 2021 mengalami kenaikan. Banyaknya komplain pelanggan terhadap buruknya pelayanan yang diberikan oleh Anteraja ini sangat berpengaruh terhadap kepercayaan pelanggan terhadap kualitas pengiriman yang diberikan dan juga jumlah transaksi yang menurun. Untuk mengidentifikasi permasalahan yang terdiri dari faktor yang mempengaruhi pelayanan tersebut dan atribut pelayanan yang perlu diidentifikasi dengan menggunakan model ServQual (ServiceQuality) dan model flower of service untuk usulan perbaikannya lalu untuk mengelempokkan layanan perusahaan yang menjadi kekuatan inti dan pendukung bisnis perusahaan. Berdasarkan perhitungan yang dilakukan menggunakan model Service Quality dapat diketahui bahwa terdapat 20 atribut pelayanan yang menentukan kepuasan pelanggan jasa pengirimana Anteraja. Atribut pelayanan tersebut berdasarkan faktor dimensi TERRA. Atribut pelayanan yang memiliki gap negatif yaitu ada 5 atribut pelayanan yang kinerjanya tidak sesuai dengan harapan pelanggan. Kelima atribut pelayanan tersebut diberikan solusi dengan menggunakan metode flower of service. Metode ini mengkategorikan pelayanan berdasarkan tiga kategori yaitu produk inti, layanan tambahan yang mempermudah, dan layanan tambahan yang memperkuat dengan melihat prioritas dari layanan yang harus diperbaiki tersebut. Usulan perbaikan yang diberikan adalah memberikan sanksi atau teguran oleh atasan kepada karyawan yang tidak bersikap jujur dan berlaku tidak adil kepada pelanggan, juga memberikan teguran kepada karyawan yang tidak serius dalam mengerjakan pekerjaannya, melakukan briefing sebelum toko di buka, mensinkronisasikan database yang ada di Gudang dan yang ada di Admin, dan memberikan pelatihan kepada customer service tentang cara menghadapi pelanggan.